2003
DOI: 10.1038/nn1043
|View full text |Cite
|
Sign up to set email alerts
|

GABA uptake regulates cortical excitability via cell type–specific tonic inhibition

Abstract: GABA(A) receptors can mediate both 'phasic' synaptic inhibition and a persistent 'tonic' form of signaling. We show that, in the presence of intact GABA uptake, guinea pig hippocampal interneurons, but not pyramidal cells, express a tonic GABA(A) receptor-mediated conductance. This conductance was pharmacologically distinct from spontaneous inhibitory postsynaptic currents (IPSCs). Inhibiting GABA uptake resulted in the expression of a comparable GABA(A) receptor-mediated tonic conductance in pyramidal cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
427
5
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(470 citation statements)
references
References 46 publications
33
427
5
5
Order By: Relevance
“…During the last decade, several studies have shown that GABA A receptor activation can also mediate tonic inhibition; these receptors are extrasynaptically and perisynaptically localized and contain a distinct, high affinity subunit composition made of δ and α4, α5 & α6 subunits (Nusser et al, 1998;Yeung et al, 2003;Semyanov et al, 2003Semyanov et al, , 2004Cope et al, 2005;Scimemi et al, 2005;Glykys et al, 2008). Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%
“…During the last decade, several studies have shown that GABA A receptor activation can also mediate tonic inhibition; these receptors are extrasynaptically and perisynaptically localized and contain a distinct, high affinity subunit composition made of δ and α4, α5 & α6 subunits (Nusser et al, 1998;Yeung et al, 2003;Semyanov et al, 2003Semyanov et al, , 2004Cope et al, 2005;Scimemi et al, 2005;Glykys et al, 2008). Hence, GABA A receptors can generate two types of current, depending on their location and subunit composition: the first type is the classic synaptic phasic (or 'transient') current that results from the release of GABA from synaptic vesicles in the synaptic cleft; the second type is a tonic ('always on') current that is caused by GABA A receptors responding to low levels of ambient GABA (Farrant and Nusser, 2005).…”
Section: Gaba a Receptor-mediated Tonic Inhibitionmentioning
confidence: 99%
“…Tonic inhibition mediated by extrasynaptic, δ subunit-containing GABARs has been identified in a number of neurons [31][32][33][34][35] and is thought to regulate neuronal excitability; however, the role of tonic inhibition in shaping behavior is unclear. The results reported here were obtained from cerebellar granule cells, a cell type for which there is strong evidence that receptors containing α6 and δ subunits are extrasynaptic 16,19,36 and are required for tonic GABA current 20,21 .…”
Section: Link Between Tonic Inhibition and Behaviormentioning
confidence: 99%
“…It has recently been shown that low concentrations of extracellular GABA may result in persistent or 'tonic' activation of extrasynaptic GABA A receptors in hippocampal interneurons, the cerebellum, and the dentate gyrus (Farrant and Nusser, 2005;Kullmann et al, 2005;Semyanov et al, 2003). Other than δ, no GABA A receptor subunits have so far been found to be exclusively extrasynaptic (Farrant and Nusser, 2005).…”
Section: Presynaptic Postsynaptic and Extrasynaptic Receptors: Phasimentioning
confidence: 99%